2018
DOI: 10.1002/prca.201600187
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Host‐Response in Cerebral Malaria Patients Using Quantitative Proteomic Analysis

Abstract: The study signifies neuronal assault due to axonal injury, altered sodium and calcium ion channels, deregulated inflammation and demyelination as a part of host response to CM. Enhanced oxidative stress, repressed oxidative phosphorylation, and demyelination of axons may contribute to the severity of the disease. Further validation of these results on a large cohort can provide leads in the development of neuroprotective therapies for CM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Platelet activation and thrombosis may precede leukocyte infiltration (88). Moreover, recent proteomic studies performed on postmortem brain tissue obtained from CM patients revealed that proteins involved in platelet activation and coagulation were upregulated (93). Thus, platelets and leukocytes (as well as platelet-leukocyte aggregates) are associated with CM.…”
Section: Malariamentioning
confidence: 99%
“…Platelet activation and thrombosis may precede leukocyte infiltration (88). Moreover, recent proteomic studies performed on postmortem brain tissue obtained from CM patients revealed that proteins involved in platelet activation and coagulation were upregulated (93). Thus, platelets and leukocytes (as well as platelet-leukocyte aggregates) are associated with CM.…”
Section: Malariamentioning
confidence: 99%
“…In recent years, plasma/serum proteomics studies have contributed substantially to elucidate the complex pathogenesis of malaria and other infectious diseases 17,18 . Intriguingly, several studies from our and other research groups have defined promising panels of plasma and serum markers in falciparum [19][20][21][22][23][24] and vivax 19,25,26 malaria. A considerable amount of further research is required to understand the complex pathophysiology of severe malaria [27][28][29] .…”
mentioning
confidence: 99%
“…In accordance with this, a recent proteomic analysis, showed that there was an increase in proteins in biological pathways involved in the innate immune response and complement system in CM patients [56]. Moreover, a pilot study looking at microarray data from a population from Mali with SM and UM showed that differential and increased expression of TLR and complement proteins was associated with disease severity [57].…”
Section: Coagulation and Inflammationmentioning
confidence: 60%